Perodua contributes RM2.6m worth of robots to UMP - UMP, PNC
Last year, the second national carmaker, Perusahaan Otomobil Kedua Sdn Bhd (Perodua), contributed 13 robots, collectively valued at RM2.6 million, to Universiti Malaysia Pahang (UMP) – reflecting one of the many efforts adopted by both industry and university to assimilate practical teaching and learning tools based on industrial requirement.